Occurrence of Podocotyle Dujardin, 1845 (Opecoelidae, Podocotylinae) in three species of deep-sea macrourids from the Gulf of Mexico and Caribbean Sea with an updated key to species and host-parasite checklist - Blend, Charles K.; Dronen, Norman O.; Armstrong, Howard W. (Zootaxa, 2019)
Podocotyle pearsei Manter, 1934 is documented from the intestine of Vaillant’s grenadier, Bathygadus melanobranchus Vaillant (Macrouridae: Bathygadinae), collected from the northeastern and western Gulf of Mexico from 783–841 m depth. The finding of P. pearsei in B. melanobranchus represents the first originally published report of this genus from this host and the fifth documented host species for P. pearsei. We report three unidentified species of Podocotyle, represented by one individual each, from the intestine of the western Atlantic grenadier, Nezumia atlantica (Parr) (Macrouridae: Macrourinae), and from Bathygadus favosus Goode & Bean (Macrouridae: Bathygadinae) found at 637 m, 710 m and 1,143 m depths in the northeastern Gulf of Mexico off Florida and from the Caribbean Sea off Colombia. We provide a checklist of the parasites known from the three macrourid species relevant to this study, comment on the biogeography of the five species of Podocotyle now known from the deep sea and discuss the low host specificity observed across this genus. The high number of fish hosts for Podocotyle (i.e. type hosts include at least 22 piscine families) encompassing a wide phylogenetic diversity and diet makes it unlikely that members of a single genus could evolve such a broad array of life histories (i.e. utilize dissimilar intermediate hosts), and we predict in the future that Podocotyle will be taxonomically divided up. Morphological and especially molecular work is needed for Podocotyle as well as for other digenean genera known to inhabit the deep sea. Podocotyle sp. 1 & 2 represent the first originally published reports of this genus from N. atlantica while Podocotyle sp. 3 represents the first report of this genus from B. favosus. Podocotyle koshari Nagaty, 1973 is declared a species inquirenda, and a dichotomous key to the 27 species of Podocotyle we recognize is provided.